Development of HOTS-Based Arabic Language Module to Improve Students' Critical Thinking Skills - Baihaqi, Ahmad Imam; Syammary, Naufal Akmal; Masrifah, Khusnul; Murtadho, Nurul; Nurhidayati, Nurhidayati (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2025)
This study aims to develop and evaluate Arabic teaching module based on Higher Order Thinking Skills (HOTS) to enhance students' critical thinking abilities. The textbook was developed using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate) and focused on reading skills. The sample included 18 students from Al-Hikmah Batu School. Data were collected through interviews, observations, tests, and documentation, yielding both qualitative and quantitative results. The findings showed that the educational materials, integrating HOTS components, were relevant to students' daily lives, covering topics like greetings, family, school, hobbies, and food. Expert assessments of content and media validity were high, with a score of 90.62%. The effectiveness test showed a significant increase in student performance, from 58.22 in the pre-test to 75.94 in the post-test. The paired sample T-test confirmed the statistical significance of the results (T = -10.050, p = 0.000), demonstrating the effectiveness of the HOTS-based reading textbook.